Survival of Homo Sapiens -A Retrospect Analysis (Global Journal of Human-Social Science, 2020)
Our understanding of human evolution is in the form of evidence of available fossil remains based on discoveries made in the last two hundred years. Most of these discoveries are incidental in nature and they do not have the correct serialization and this evidence is not documented in the true sense. In the context of human evolution we discuss the processes under which a pre-human species with a large brain evolved into modern human. In this context, we must pay attention to the known early forms of human beings. Most of them are now extinct and are known only by their fossil remains and material culture. Now, the question arises in front of us whether all humans were direct ancestors of same species or were their sub-sections or sub branching of the lineage in human evolution? Based on the fossil material presently available, we can say that some of them are from the human lineage of evolution. If they were related, then there are some forms of species that existed before hybridization. Genetic groups found today are formed by hybridizing of genetic traits. Homo sapiens were the only ones who have been transformed into modern humans through the process of evolution. Why the species which became extinct despite being homo genus is a question in itself.
Keywords: homo; evolution; fossils remains; prehistoric environment